Antecedents and Consequences of Consumer Attitudes towards Advertising on Social Media - Fikri, M Husnul; Risqiani, Renny (Universitas Trisakti, 2023)
Social media has developed and created new advertising systems for business and commerce purposes. Previous research found that many factors influence a person's interest in advertisements displayed on social media. This study aims to examine the effect of advertising value on attitudes towards social media advertising (SMA) and attitudes towards SMA on attitudes towards brands and purchase intentions. The study was conducted on 267 respondents who often interact through social media. Data were analyzed using Structural Equation Modeling (SEM) with the help of smartPLS software. The results showed that the trustworthiness and personalization of advertisements delivered through social media were able to influence consumer attitudes towards these advertisements. Attitudes towards social media advertising can influence consumer attitudes towards advertised brands. Furthermore, brand attitude has a greater influence on purchase intention than attitude towards SMA. Meanwhile, perceived incentives and perceived encroached risk have no significant effect on attitude to social media advertisement. Keywords: Advertising Value, Attitude to Social Media Advertising, Brand Attitude, and Purchase Intention